2013
DOI: 10.1159/000350244
|View full text |Cite
|
Sign up to set email alerts
|

Virilization of a Young Girl Caused by Concomitant Ectopic and Intra-Adrenal Adenomas of the Adrenal Cortex

Abstract: Background: Adenomas of the adrenal gland are rare causes of virilization in childhood. Case Report: A girl aged 2 years and 4 months presented with pubarche, distinct clitoral hypertrophy, tall stature, and increased height velocity. Plasma testosterone and dehydroepiandrosterone were elevated. Androgens remained unchanged after adrenocorticotropic hormone, and dexamethasone administrations. Ultrasound examination and magnetic resonance imaging indicated an extra-adrenal mass adjacent to the left adrenal glan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…Although early 75 Se-selenomethyl-19-norcholesterol studies showed promising results, scintadren is currently no longer available for clinical studies and has been replaced by 131 I-iodomethyl-norcholesterol (NP-59) [25]. In a declining number of cases, NP-59 continues to be used to investigate the secretory status of adrenal adenomas and aid lesion lateralization [26,27,28,29,30,31]. However, these techniques have significant shortcomings including delivery of a relatively high radiation dose to the adrenal glands, time-consuming acquisition protocols, a requirement for the patient to take a 7–10 day course of high-dose glucocorticoids to suppress non-autonomous hormone synthesis and low sensitivity with poor spatial resolution (traditionally only allowing reliable detection of lesions >2 cm in diameter, although single photon emission computed tomography (SPECT) may afford improved resolution).…”
Section: Norcholesterol Scintigraphy—historical Perspectivementioning
confidence: 99%
“…Although early 75 Se-selenomethyl-19-norcholesterol studies showed promising results, scintadren is currently no longer available for clinical studies and has been replaced by 131 I-iodomethyl-norcholesterol (NP-59) [25]. In a declining number of cases, NP-59 continues to be used to investigate the secretory status of adrenal adenomas and aid lesion lateralization [26,27,28,29,30,31]. However, these techniques have significant shortcomings including delivery of a relatively high radiation dose to the adrenal glands, time-consuming acquisition protocols, a requirement for the patient to take a 7–10 day course of high-dose glucocorticoids to suppress non-autonomous hormone synthesis and low sensitivity with poor spatial resolution (traditionally only allowing reliable detection of lesions >2 cm in diameter, although single photon emission computed tomography (SPECT) may afford improved resolution).…”
Section: Norcholesterol Scintigraphy—historical Perspectivementioning
confidence: 99%
“…All signs indicated the benign tendency of this mass. Recently, some molecular markers have been used to differentiate adrenal carcinoma from benign tumors [ 7 ]. These new markers may help to distinguish the nature of tumor in the future.…”
Section: Discussionmentioning
confidence: 99%